Employee performance evaluation by the AHP: a case study - Islam, Rafikul; Mohd Rasad, Shuib (National Cheng Kung University, 2006)
Employee performance evaluation is designed to assess each individual’s contribution to the organization. The performance of individuals against organizational goals determines whether the organization meets its goals. The basic objectives of performance evaluations are two-fold: firstly to reward employees for meeting organizational objectives and secondly to identify which objectives are not met and to develop action plans to ensure they are achieved in future. The present paper uses analytic hierarchy process (AHP) to evaluate employees performances based upon the criteria: quantity/quality of the work, planning/organization, initiative/commitment, teamwork/cooperation, communication and external factors. Each of these criteria has been divided into 3 subcriteria. Two hundred and ninety-four employees of Inter System Maintenance Services Sdn. Bhd. are evaluated on these subcriteria. Overall ranking of the employees has been obtained using the absolute measurement procedure of AHP.